2020
DOI: 10.3892/mco.2020.2050
|View full text |Cite
|
Sign up to set email alerts
|

Elemental diet directly affects chemotherapy‑induced dermatitis and raw wound areas

Abstract: Elental ® is an L-glutamine-rich elemental diet (ED) that has been widely used in Japan as a nutritional supplement for malnourished patients. In addition, Elental ® has been successfully used in the management of chemotherapy-induced mucositis in cancer patients. Recently, it was also reported that Elental ® can effectively reduce chemotherapy-induced oral mucositis in patients with oral squamous cell carcinoma, and can also reduce mucositis and dermatitis in animal models. However, it is unclear whether oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…We have been using Elental ® for treating malnutrition in patients undergoing chemotherapy in recent years. Moreover, we observed that Elental ® improved chemotherapy-induced oral mucositis (25)(26)(27)(28). Based on our previous data, we hypothesized that Elental ® or Elental ® components may protect salivary glands, preserve saliva secretion volume and alleviate oral mucositis by improving the oral environment.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have been using Elental ® for treating malnutrition in patients undergoing chemotherapy in recent years. Moreover, we observed that Elental ® improved chemotherapy-induced oral mucositis (25)(26)(27)(28). Based on our previous data, we hypothesized that Elental ® or Elental ® components may protect salivary glands, preserve saliva secretion volume and alleviate oral mucositis by improving the oral environment.…”
Section: Discussionmentioning
confidence: 84%
“…Several clinical studies showed the beneficial effects of Elental ® against chemotherapy-induced mucositis in cancer patients (23,24). Animal studies have shown that ED with glutamine may protect the gut from chemotherapeutic agents and radiation, and can help in the treatment of chemotherapy-induced mucositis and dermatitis (7,9,25,26). We also reported the healing effects of Elental ® against chemotherapy-induced mucositis and dermatitis in head and neck cancer patients (27,28).…”
mentioning
confidence: 77%
“…Over the past few years, the usefulness of EDs against the negative side effects of antineoplastic drugs has been observed in patients with cancer at Yamaguchi University Hospital. Elental ® was effective against chemotherapy-and/or radiotherapy-induced mucositis and dermatitis in HNC patients, as well as in vitro and in vivo (21,22,42,43). Based on these results, it was hypothesized that Elental ® may help to alleviate oral mucositis by preserving saliva secretion volume and improving the oral environment.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients complained of any irritation, pain or difficulty during oral administration (22). Moreover, murine back skin wounds are healed by topical application of Elental ® , which suggests that it may have direct soothing effects on the wounded areas upon contact (43). Therefore, it was assumed that Elental ® is suitable for patients with severe oral mucositis who are unable to eat solid foods.…”
Section: Discussionmentioning
confidence: 99%
“…In nude mice with 5-FU-induced dermatitis, oral ED decreased the expression of tumor necrosis factor-a, interleukin-1b, and interleukin-6, and decreased the transcriptional activation of NF-kB in keratinocytes, suggesting that ED may alleviate dermatitis and other inflammatory conditions induced by anticancer therapy [32]. ED also promoted the growth and migration of human oral keratinocytes, suggesting that it might minimize dermatitis and possibly oral mucositis by directly stimulating the development of these cells [33].…”
Section: The Edmentioning
confidence: 95%